Desenvolvimento de um processo de reparo por atrito para peças com trincas passantes - Santos, Erasto José dos (2013)
In this work, a new friction tapered plug welding (FTPW) process is used to remove through-wall cracks. In order to remove the crack, a retention plate is attached at the back of the plate to be repaired, so that at the end effect it may be assumed as a repairing process using a blind hole. Another innovation was introduced by using different gaps between the plate to be repaired and the retention plate, allowing an additional flowing path for the plasticized material and so a better elimination of oxide layers in the bonding interface. Tests were carried out using blocks made of ASTM A36 and pins of ABNT 1010, and axial forces of 60, 80, 100 and 120 kN. The welding quality was evaluated by means of metallographic examination, microhardness and bending tests. The results showed that a good metallurgical bond and no crack were observed in the bending test. Nevertheless, tests conducted with a clearance between the base and the opposing plate showed that it may lead to incomplete filling of the hole. Therefore it has to be strictly controlled during the process.